Cdk5‐mediated phosphorylation regulates phosphatidylinositol 4‐phosphate 5‐kinase type I γ 90 activity and cell invasion. Issue 1 (24th July 2018) - Li, Liqing; Kołodziej, Tomasz; Jafari, Naser; Chen, Jing; Zhu, Haining; Rajfur, Zenon; Huang, Cai
ABSTRACT: Phosphatidylinositol 4‐phosphate 5‐kinase type I γ (PIPKIγ90) regulates cell migration, invasion, and metastasis. However, it is unknown how cellular signals regulate those processes. Here, we show that cyclin‐dependent kinase 5 (Cdk5), a protein kinase that regulates cell migration and invasion, phosphorylates PIPKIγ90 at S453, and that Cdk5‐mediated PIPKIγ90 phosphorylation is essential for cell invasion. Moreover, Cdk5‐mediated phosphorylation down‐regulates the activity of PIPKIγ90 and the secretion of fibronectin, an extracellular matrix protein that regulates cell migration and invasion. Furthermore, inhibition of PIPKIγ activity with the chemical inhibitor UNC3230 suppresses fibronectin secretion in a dose‐dependent manner, whereas depletion of Cdk5 enhances fibronectin secretion. With total internal reflection fluorescence microscopy, we found that secreted fibronectin appears as round dots, which colocalize with Tks5 and CD9 but not with Zyxin. These data suggest that Cdk5‐mediated PIPKIγ90 phosphorylation regulates cell invasion by controlling PIPKIγ90 activity and fibronectin secretion.—Li, L., Kotodziej, T., Jafari, N., Chen, J., Zhu, H., Rajfur, Z., Huang, C. Cdk5‐mediated phosphorylation regulates phosphatidylinositol 4‐phosphate 5‐kinase type I γ 90 activity and cell invasion. FASEB J. 33, 631–642 (2019). www.fasebj.org